Teknologi Edukasi Perawatan Bayi Prematur - Wardhani, Rachmayanti Purawita; Allenidekania, Allenidekania; Rustina, Yeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the most effective technology for preterm infant care, so as to improve knowledge, maternal skills and growth of preterm infants. The research method used was systematic review using five databases, namely Proquest, ScienceDirect, Emeraldinsight, PubMed, ClinicalKey. The results showed that 10 research articles could improve the knowledge, skills, and growth of preterm infants, such as: Booklet, tele-rehabilitation-based educational technology EI (Early Intervention), Family Integrated Care and Mobile Technology (m-FiCare m-Health, Telenursing education of premature, web application. Conclusion The most effective educational technology and has the advantage of accessing education is the web. Keywords: Baby Care, Premature, Technology